Exploring medication self-management in polypharmacy: a qualitative systematic review of patients and healthcare providers perspectives - Jin, Ran; Liu, Caiyan; Chen, Jinghao; Cui, Mengjiao; Xu, Bo; Yuan, Ping; Chen, Lu (Frontiers in Pharmacology, 2024)
Purpose Polypharmacy presents many challenges to patient medication self-management. This study aims to explore the self-management processes of medication in polypharmacy from the perspectives of both patient and healthcare provider, which can help identify barriers and facilitators to effective management. Methods A systematic review of qualitative studies was performed by searching seven databases: PubMed, Web of Science, Cochrane Library, Embase, CINAHL, PsycINFO, and MEDLINE, from their establishment until August 2024. The Critical Appraisal Skills Programme (CASP) tool was employed to evaluate the quality of the studies included. The extracted data were then analysed thematically and integrated into The Taxonomy of Everyday Self-management Strategies (TEDSS) framework. Result A total of 16 studies were included, involving 403 patients and 119 healthcare providers. Patient management measures were mapped into TEDSS framework, including categories such as medical management, support-oriented domains and emotional and role management. Conclusion Enhancing patients' proactive health awareness, improving medication literacy, balancing lifestyle adjustments with medication therapy, dynamically reviewing and optimizing medications, strengthening patients' social support networks, and helping patients integrate medication management into their daily life are the key elements that can effectively assist patients in self-managing their medications. Future interventions to improve patient medication selfmanagement ability should be designed for these issues. This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO), with the registration number CRD42024524742.